The research trend of the undergraduate seminar papers of the University of the Philippines Manila, College of Dentistry (UPCD) From 1999-2013 - Aman, Angeline Beatrice L.; Reyes, Veronica M.; Sy, Chanel Isseline D.; Rebueno Santos, Jessica (Manila: Department of Community Dentistry, University of the Philippines Manila,c2017.)
The University of the Philippines Manila supports the state's effort to advance the health of the Filipinos by improving the country's aptitude for health research and development. Research encourages the continued progress of the entire higher education sector. For this reason, it is vital for us to scrutinize the quantity and quality of undergraduate researches being produced per year, and see how these have changed. Our aim is to determine the research trend of the UPCD undergraduate seminar papers from 1999 to 2013. A similar study published in Brazil on 2011 by Scariot, Stadler, Assuncao, Pintarelli, and Ferreira titled "A Map of Brazilian Dental Research in the Last Decade" is being modelled by this paper.
Materials and Methods: Total enumeration of all UPCD undergraduate seminar papers from 1999-2013 was done. These were coded and classified according to the different fields of knowledge in Dentistry using the abstract. The categories are: Oral Medicine, Operative Dentistry, Prosthodontics, Orthodontics, Basic Dental Sciences, Population-based Oral Health and UPCD Students' Welfare and Concerns. Selected terms/keywords determined to be highly associated with a specific category were used to systematically group the papers into their proper categories, from which the yearly trends were obtained and analysed.
Results: The research trend of UPCD seminar papers showed recurring low interest on specialized and new disciplines. Students prefer to research the basic fields of dentistry. The most frequently studied topics were those concerning Students, Patients and Practitioners' Welfare and Concerns, Population based Oral Health and Basic Dental Sciences. The average time it took for a seminar paper to be produced after an oral health event was found to be 3.33 years. The only development in the research output is super oxide water.
3 Conclusion: From 1999-2013, the top 3 topics that UPCD students are particularly interested in examining are those that are related to Students, Patients and Practitioners' Welfare and Concerns (26.85%), Population-based Oral Health (18.06%), and Basic Dental Sciences (16.09%). The rest of the trend is as follows: Oral Medicine (13.72%), Alternative Medicine (8.68%), Operative Dentistry (6.60%), and Prosthodontics (4.98%). Generating the least amount of interest are topics concerning Orthodontics (2.08%), New Innovations (1.39%), and Others (1.22%). A significant number (71.2%) of the seminar papers produced do not follow current global and national trends.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dentistry--Research.; Oral Health; Oral Health Events; Research Trends